2020
DOI: 10.3390/antiox9080741
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Seminal Plasma GSTM3 as a Quality and In Vivo Fertility Biomarker in Pigs—Relationship with Sperm Morphology

Abstract: Glutathione S-transferases Mu 3 (GSTM3) is an essential antioxidant enzyme whose presence in sperm has recently been related to sperm cryotolerance, quality and fertility. However, its role in seminal plasma (SP) as a predictor of the same sperm parameters has never been investigated. Herein, cell biology and proteomic approaches were performed to explore the presence, origin and role of SP-GSTM3 as a sperm quality and in vivo fertility biomarker. GSTM3 in SP was quantified using a commercial Enzyme-Linked Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…However, when samples were divided considering breeds, no effect on SP-metabolites concentration was observed, except for fumarate, which exhibited higher levels in Pietrain than in Duroc boars. This agrees with most of the studies evaluating SP components in samples from different pig breeds, in which no breed effect was reported (Barranco et al, 2015b(Barranco et al, , 2016(Barranco et al, , 2020Llavanera et al, 2020). However, since the sample size for each breed was limited in the present study, further research should verify this assumption.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, when samples were divided considering breeds, no effect on SP-metabolites concentration was observed, except for fumarate, which exhibited higher levels in Pietrain than in Duroc boars. This agrees with most of the studies evaluating SP components in samples from different pig breeds, in which no breed effect was reported (Barranco et al, 2015b(Barranco et al, , 2016(Barranco et al, , 2020Llavanera et al, 2020). However, since the sample size for each breed was limited in the present study, further research should verify this assumption.…”
Section: Discussionsupporting
confidence: 90%
“…Many efforts have been focused on exploring pig SP composition with the aim to uncover SP biomarkers able to predict semen quality after ejaculate collection (López Rodríguez et al, 2012;Barranco et al, 2016Barranco et al, , 2017Barranco et al, , 2020Llavanera et al, 2020). In the last years, the advances in metabolomic analytical methods have allowed the identification of SP-metabolites as potential sperm quality biomarkers in mammalian species, such as humans (Bonechi et al, 2015;Engel et al, 2019;Wang et al, 2019;Mumcu et al, 2020;Xu et al, 2020) and cattle (Moura et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers for sperm dysfunction [ 218 ] and (in)fertility have been detected in spermatozoa [ 27 , 190 , 219 , 220 ] and in the SP [ 221 , 222 ] of many species, including humans [ 218 , 222 , 223 , 224 , 225 ] and livestock [ 70 , 226 ]. They vary from gene presence [ 227 ], markers of Sertoli cell function [ 228 ], proteins [ 36 , 229 , 230 , 231 ], anti-oxidative enzymes [ 223 , 232 , 233 ] and metabolites [ 234 , 235 , 236 ] to exosome-associated molecules [ 237 , 238 ] and microRNAs [ 181 , 239 , 240 , 241 ].…”
Section: What Else Can Be Done With Our Current Knowledge Of Sp?mentioning
confidence: 99%
“…Our data also report the presence of this protein in the seminal plasma of dolphins. Recently, it has been demonstrated that low concentration of GSTM3 in pig seminal plasma is related to an increased percentage of sperm abnormalities (Llavanera et al, 2020a). ROPN1 protein is found in sperm flagellum as part of the fibrous sheath, specifically located in the principal piece and end piece of the flagellum (Fujita et al, 2000;Chen et al, 2011).…”
Section: Proteins Identified In the Spermatozoa Of Bottlenose Dolphinmentioning
confidence: 99%